Health Disparities, Risk Behaviors and Healthcare Utilization among Transgender Women in Los Angeles County: A Comparison from 1998–1999 to 2015–2016 - Reback, Cathy J. (AIDS Behav, 2018)
Data from two studies of transgender women in Los Angeles County that used the same methodology and survey assessment (Study 1: 1998–1999, N=244; Study 2: 2015–2016, N=271), compared structural determinants of health, HIV/STI prevalence, HIV risk behaviors, substance use, gender confirmation procedures, and perceived discrimination and harassment/abuse across a 17-year time period. Findings demonstrated that participants in the latter study reported significantly higher access to healthcare insurance and prescription hormones. However, participants in the latter study also reported lower levels of income; and, elevated prevalence of homelessness, HIV and lifetime STIs, receptive condomless anal intercourse with casual partner(s), and reported physical harassment/abuse. Given the timeframe of these results, these findings elucidate specific areas of transgender women’s health and risk profiles that improved or worsened across 17 years. While healthcare access has improved, transgender women continue to face significant barriers to good health, indicating the need for increased attention to this population.